2015
DOI: 10.1007/s11064-015-1619-9
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated Analogues of the Neurotransmitter GABA: trans-4-Aminocrotonic, cis-4-Aminocrotonic and 4-Aminotetrolic Acids

Abstract: Analogues of the neurotransmitter GABA containing unsaturated bonds are restricted in the conformations they can attain. This review traces three such analogues from their synthesis to their use as neurochemicals. trans-4-Aminocrotonic acid was the first conformationally restricted analogue to be extensively studied. It acts like GABA across a range of macromolecules from receptors to transporters. It acts similarly to GABA on ionotropic receptors. cis-4-Aminocrotonic acid selectively activates bicuculline-ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The involvement of a nitrogen atom is particularly important in formation of bioactive materials, such as unsaturated amino acids. The unsaturated (α,β)-dehydroamino acids, for instance, are important pharmaceutical targets. , As a model for CHAT -assisted amino–imino tautomerization, we employed the conversion of amino isomer of the unsaturated GABA (γ-aminobutyric acid), H 2 N–CH = CH–CH 2 –C­(O)­OH, into its imino (enamine) form, HN = CH–CH 2 –CH 2 –C­(O)­OH. Our calculations revealed that the Gibbs energy barrier for amino–imino tautomerization via a CHAT mechanism, indeed, is lower than the barrier for direct isomerization by more than a factor of 2 (30.55 vs 65.67 kcal/mol).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of a nitrogen atom is particularly important in formation of bioactive materials, such as unsaturated amino acids. The unsaturated (α,β)-dehydroamino acids, for instance, are important pharmaceutical targets. , As a model for CHAT -assisted amino–imino tautomerization, we employed the conversion of amino isomer of the unsaturated GABA (γ-aminobutyric acid), H 2 N–CH = CH–CH 2 –C­(O)­OH, into its imino (enamine) form, HN = CH–CH 2 –CH 2 –C­(O)­OH. Our calculations revealed that the Gibbs energy barrier for amino–imino tautomerization via a CHAT mechanism, indeed, is lower than the barrier for direct isomerization by more than a factor of 2 (30.55 vs 65.67 kcal/mol).…”
Section: Resultsmentioning
confidence: 99%
“…The unsaturated (α,β)-dehydroamino acids, for instance, are important pharmaceutical targets. 67,68 As a model for CHATassisted amino−imino tautomerization, we employed the conversion of amino isomer of the unsaturated GABA (γaminobutyric acid),…”
Section: Skeletal Double-bond Shift (Dbs) and The Effect Ofmentioning
confidence: 99%
“…Muscimol is such a conformationally restricted GABA analogue, containing both a ring structure and double bonds, acting selectively on GABA A receptors (Johnston et al, 1968). One of us (Graham Johnston) has reviewed unsaturated analogues of GABA (Johnston, 2016) in a special issue of Neurochemical Research honouring the other (Philip Beart; may underlie its complex functions. The need for new chemical entities with selective actions for further studies highlights the need for continuing collaboration between chemists and biologists.…”
Section: G Aba Chemis Trymentioning
confidence: 99%
“…Muscimol is such a conformationally restricted GABA analogue, containing both a ring structure and double bonds, acting selectively on GABA A receptors (Johnston et al., 1968). One of us (Graham Johnston) has reviewed unsaturated analogues of GABA (Johnston, 2016) in a special issue of Neurochemical Research honouring the other (Philip Beart; Lawrence & Gundlach, 2016). This was reciprocating a special issue of Neurochemical Research honouring a significant birthday of the other (Graham Johnston; Beart & Balcar, 2009).…”
Section: Gaba Chemistrymentioning
confidence: 99%
“…Additionally, molecules unable to cross the BBB, must rely on various endogenous transporters. [13] Some GABA analogues that are unsaturated between the amino and carboxylic group, including cis-amino crotonic acid, trans-amino crotonic acid, and aminotetrolic acid, are characterized by an increased specificity to recognize GABAergic receptors; [14][15][16][17] similarly, cyclic systems, such as gabaculine, a naturally occurring neurotoxin, analog of m-aminobenzoic acid (MABA) and GABA-AT inhibitor, are able to cross the BBB (Figure 1) [18][19][20] and these structures are closely related with our proposed compounds in the Table 1.…”
Section: Introductionmentioning
confidence: 99%